UPAYA PERLINDUNGAN HUKUM PADA KONSUMEN DALAM TRANSAKSI E-COMMERCE UNTUK MENDUKUNG PERTUMBUHAN EKONOMI DIGITAL DI INDONESIA - Bernada, Tetanoe (Jurnal Hukum dan Peradilan, 2017)
The business transaction method has changed, from â€œreal worldâ€ to virtual world.Â  This phenomenon provokes many legal problems for consumers where consumers often do not have a strong bargaining position and have a weak position. The e-commerce industry in Indonesia grows rapidly in the middle of economic slowdown pace. The value of e-commerce in Indonesia in 2016 is estimated to reach 30 billion US dollars or equivalent to Rp 395 trillion. The figure is predicted to rise to 130 billion US dollars or equivalent to Rp 1.714 trillion in 2020. The government should regulate the legal protection for consumer especially based on its actualization and urgency. The aim of this protection is to fulfill legal certainty which is needed both for business transaction and consumer rights protection. Furthermore, the legal protection of consumer rights in e-commerce should be given in whole aspects of law both simultaneous and comprehensive protection.Keywords: legal protection efforts, consumers, e-commerce